Production and Marketing of Apple Fruit Crop- a Study Premise to Shimla District of Himachal Pradesh, India - Mehta, Piyush; Thakur, Rajesh Kumar; Chauhan, Sachin (International Journal of Bio-resource and Stress Management, 2023)
The climate of dry temperate region of Himachal Pradesh is suitable for growing the wide range of temperate fruits such as apple, pear, plum, apricot and peach. The market structure of temperate fruits is going through a lot of changes in terms to build marketing links in terms to fetch lucrative market. Moreover, it also considers the high transportation cost, lack of storage facilities, non availability of better means of transportation and exploitation by middle men. The study has focused on management practices adopted by farmers in reference to manage the production and marketing activities of apple fruit crop. It has identified the marketing channel through which the apple fruit growers may safely dispose of their produce, which infact other temperate fruit growers can also gain benefits from the same.